2016
DOI: 10.1177/0734242x16634196
|View full text |Cite
|
Sign up to set email alerts
|

Effects and optimization of the use of biochar in anaerobic digestion of food wastes

Abstract: The addition of various amounts of biochar to anaerobic digestion of food wastes at different ratios of inoculum to substrate (ISR) was investigated to evaluate the effect of biochar as a functional additive and to optimize the additive dosage of biochar. The biochar treatments at ISR 2, 1, and 0.8 shortened the lag phase of digestion by -20.0%-10.9%, 43.3%-54.4%, and 36.3%-54.0%, and raised the maximum methane production rate by 100%-275%, 100%-133.3%, and 33.3%-100%, respectively, compared to control without… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
54
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 141 publications
(62 citation statements)
references
References 33 publications
6
54
1
1
Order By: Relevance
“…In the single other study dealing with biochar addition during FW AD, biochar supplementation improved the kinetics of methane production in batch reactors, dividing by two the lag phases and increasing the maximum methane production rates. 45 Considering the obtained results and other scientific studies, it can be hypothesized that the improved VFA degradation kinetics could be related to a enhancement of the syntrophic interactions between microorganisms via biofilm formation and to the occurrence of DIET. Biochar has been found to promote the growth of bacteria known to participate in DIET (i.e.…”
Section: Biochar and Industrial Fecl 3 Dosing As Feasible Option For mentioning
confidence: 63%
See 3 more Smart Citations
“…In the single other study dealing with biochar addition during FW AD, biochar supplementation improved the kinetics of methane production in batch reactors, dividing by two the lag phases and increasing the maximum methane production rates. 45 Considering the obtained results and other scientific studies, it can be hypothesized that the improved VFA degradation kinetics could be related to a enhancement of the syntrophic interactions between microorganisms via biofilm formation and to the occurrence of DIET. Biochar has been found to promote the growth of bacteria known to participate in DIET (i.e.…”
Section: Biochar and Industrial Fecl 3 Dosing As Feasible Option For mentioning
confidence: 63%
“…observed that biochar supplementation increased the methane production rates and enhanced the consumption of HAc and HBu in the second stage of a 2‐phase AD reactor treating aqueous FW. In the single other study dealing with biochar addition during FW AD, biochar supplementation improved the kinetics of methane production in batch reactors, dividing by two the lag phases and increasing the maximum methane production rates …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, this would result in a decrease in the microbial lag phase (Fagbohungbe et al, 2016(Fagbohungbe et al, , 2017. Biochar added in the AD can also optimize and balance the trace minerals, micronutrients and macronutrients, buffering agents, compounds able to mitigate ammonia inhibition, and substances with high biomass immobilization capacity; remove the toxic materials; and enhance the degradation rate of dissolved organics and VFAs (Cai et al, 2016). Moreover, the direct addition of biochar would enhance significantly the production rate of H 2 , which favors the hydrogenotrophic methanogenic route of the AD process (Sunyoto et al, 2016).…”
Section: Introductionmentioning
confidence: 99%